Salvage therapy for localized recurrences of penile cancer. Issue 3 (May 2021) - Saidian, Ava; Ceballos, Brian; Necchi, Andrea; Baumgarten, Adam S.; Spiess, Philippe E.
Abstract : Purpose of review: To review the current literature and guidelines regarding salvage therapy for local and regional recurrence of primary penile cancer. Recent findings: While invasive surgical management has not significantly changed, penile sparing treatments (PSTs) may have a promising role in the management of local recurrence. Penile sparing surgeries do appear to have higher rates of recurrence. However, the overall survival rate is comparable to that of partial and total penectomies. Additionally, a combination of therapies may have a more profound effect on management of penile cancer. Summary: Clinicians must discuss the role of each type of therapy for penile cancer with their patients, and tailor their management to the extent of disease in each patient. While it is important to discuss the balance between quality of life and rates of relapse, one must also emphasize the rates of overall survival in patients with local recurrence who are treated with PSTs.